2021
DOI: 10.1101/2021.03.05.434121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell Aging Impairs the Self-Organizing Capacity of Lung Alveolar Epithelial Stem Cells

Abstract: Multicellular organisms maintain structure and function of tissues/organs through emergent, self-organizing behavior. In this report, we demonstrate a critical role for lung mesenchymal stromal cell (L-MSC) aging in determining the capacity to form 3-dimentional organoids or alveolospheres with type 2 alveolar epithelial cells (AEC2s). In contrast to L-MSCs from aged mice, young L-MSCs support the efficient formation of alveolospheres when co-cultured with young or aged AEC2s. Aged L-MSCs demonstrated features… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition to the shift of WNT proteins in lung ageing, there is also evidence showing ageing-associated dysregulation of WNT target genes. Several WNT target genes including Tle1, Lef1, Nkd1 (Hofmann et al 2014), Ccnd2 (Cyclin D2), Ccna1 (Cyclin A1) (Watson et al 2020) were found to be reduced in the ageing mouse lung, while c-Myc (Zhang et al 2012a) and Wisp-1 (Chanda et al 2021) show increased expression. Another study exploring differential expression of WNT target genes in the ageing mouse lung (Hofmann et al 2014) also observed a decrease in WNT/β-catenin signalling with age on a whole lung level.…”
Section: Normal Lung Ageingmentioning
confidence: 98%
“…In addition to the shift of WNT proteins in lung ageing, there is also evidence showing ageing-associated dysregulation of WNT target genes. Several WNT target genes including Tle1, Lef1, Nkd1 (Hofmann et al 2014), Ccnd2 (Cyclin D2), Ccna1 (Cyclin A1) (Watson et al 2020) were found to be reduced in the ageing mouse lung, while c-Myc (Zhang et al 2012a) and Wisp-1 (Chanda et al 2021) show increased expression. Another study exploring differential expression of WNT target genes in the ageing mouse lung (Hofmann et al 2014) also observed a decrease in WNT/β-catenin signalling with age on a whole lung level.…”
Section: Normal Lung Ageingmentioning
confidence: 98%